Responsible use of artificial intelligence in scientific writing - Castillo Castro, Gladys Paulina (2025)
Dear Editor: We have read with great interest the article by Cornelio Gonzales Torres, published in volume 2025-2 of Revista Horizonte Médico (1), which analyzes the importance of using of artificial intelligence (AI) by researchers in the preparation of scientific papers—while not neglecting the application of ethical and moral values—in an environment where these tools are growing exponentially, now exceeding 24,000 AI systems. The author also emphasizes the need for professionals from various fields to foster critical thinking both for regarding their use and in recognizing the advantages and disadvantages of their application in scientific output.